Analisis Produksi Terhadap Pendapatan Pengerajin Dulang Fiber di Desa Bresela Kabupaten Gianyar - Dwitasari, Ni Made Marsy; Indrajaya, I Gusti Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 5, Mei 2017 (pp. 677 - 919), 2017)
Normal 0 false false false EN-US X-NONE X-NONE Gianyar is a regency/city of art that have excelled in the field of small creative industries. The industry made a major contribution to the welfare of the community to reduce unemployment. This study aimed to analyze the influence of capital, hours of work, and education on craft production in Dulang Fiber Village Bresela Gianyar regency. Effect of production to earnings craftsmen Dulang Fiber in the Village Bresela Gianyar regency. Variable production as an intervening variable capital influence, hours of work, and education to earnings craftsmen Dulang Fiber in the Village Bresela Gianyar regency. Methods of data collection in research by interview and observation using a questionnaire. The analysis technique using path analysis. The results of data analysis capital amounted to 0.474 positive effect on production, capital has the most effect on production. Hours of work amounted to 0.148 positive effect on production. Education positive effect amounting to 0,044 on the production and the production of a positive effect on revenues amounting to 0.998 craftsmen Dulang Fiber. Production variables influence an intervening variable capital, hours of work, and education to earnings craftsmen Dulang Fiber. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:24.0pt; mso-para-margin-right:0in; mso-para-margin-bottom:0in; mso-para-margin-left:0in; mso-para-margin-bottom:.0001pt; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: modal, jam kerja, pendidikan, produksi, pendapatan